1998
DOI: 10.1001/archopht.116.4.449
|View full text |Cite
|
Sign up to set email alerts
|

Cataract Surgery and Intraocular Lens Implantation in Patients With Retinoblastoma

Abstract: To report the visual outcome and complications after extracapsular cataract extraction with posterior chamber intraocular lens (IOL) implantation in eyes that underwent external beam radiotherapy for the treatment of retinoblastoma. Methods: Eleven eyes of 8 patients aged 1.5 to 8.0 years at the time of surgery for irradiation-induced cataract were observed for 6 to 39 months (mean [±SD], 20±10 months). A standard technique of extracapsular cataract extraction, posterior chamber IOL implantation, pars plana po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…In the present study, postoperative inflammation was moderate in children receiving radiation therapy. This was also noted by Portellos and Buckley in their 11 cases study and was attributed to the destruction by the radiotherapy of the antigenic lens proteins and cells 20. In contrast with studies in which pars plana lensectomy was the predominant surgical technique performed,21–24 we did not observe any case of postoperative retinal detachment.…”
Section: Discussionsupporting
confidence: 57%
“…In the present study, postoperative inflammation was moderate in children receiving radiation therapy. This was also noted by Portellos and Buckley in their 11 cases study and was attributed to the destruction by the radiotherapy of the antigenic lens proteins and cells 20. In contrast with studies in which pars plana lensectomy was the predominant surgical technique performed,21–24 we did not observe any case of postoperative retinal detachment.…”
Section: Discussionsupporting
confidence: 57%
“…Same authors (15) reported a series of eleven eyes that underwent a primary IOL implantation after RB treatment. They concluded that IOL implantation seemed to be a safe method for aphakia correction.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that IOL implantation seemed to be a safe method for aphakia correction. The authors advised penetrating the anterior chamber through a clear corneal incision to avoid direct contact with conjunctival blood vessels, scleral tissues, and vitreous management in order to reduce the risk of spreading tumoral cells (15) . Besides tumoral spread or recurrences, the complications expected in the removal of radiation-induced cataracts are similar to pediatric cataract surgery (3,9,(16)(17) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that cataract surgery in patients who have previously received radiation therapy for retinoblastoma is generally not associated with tumor recurrence or spread (Brooks et al, 1990;Portellos and Buckley, 1998). Controversies in cataract management include the surgical approach, the management of the posterior capsule and anterior vitreous.…”
Section: Retinoblastomamentioning
confidence: 99%